2016
DOI: 10.1097/01.naj.0000482953.88608.80
|View full text |Cite
|
Sign up to set email alerts
|

Ce

Abstract: Some nurses who work the night shift experience high levels of sleepiness. Napping has been adopted as an effective countermeasure to sleepiness and fatigue in other safety-sensitive industries but has not had widespread acceptance in nursing. In this two-hospital implementation project, napping was offered to six nursing units where nurse executives had previously approved nap implementation for the night shift as a pilot project. Successful implementation occurred in only one of the six units with partial su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…However, peripheral clock gene expression was not significantly different among groups (Bracci et al, 2013). The results confirm there is a trend such that the breast cancer risk may is lower for those who take night-shift napping than non-nappers.…”
Section: Urinary Melatonin 17-β-estradiol and Clock Gene Expressionsupporting
confidence: 57%
See 4 more Smart Citations
“…However, peripheral clock gene expression was not significantly different among groups (Bracci et al, 2013). The results confirm there is a trend such that the breast cancer risk may is lower for those who take night-shift napping than non-nappers.…”
Section: Urinary Melatonin 17-β-estradiol and Clock Gene Expressionsupporting
confidence: 57%
“…The total sample size of this studies was 4,701, with 2,592 nurses (55%) having naps during night-shift. Ten studies reported the length of nurses' napping at night-shift (Barthe et al, 2016;Bracci et al, 2013;Castro et al, 2015;Daurat & Foret, 2004;Ribeiro-Silva et al, 2006;Rotenberg et al, 2016;Silva-Costa et al, 2011Takahashi et al, 1999), which varies depending on the length of their The time devoted to sleep/rest per working night did not differ between those who work more and those who work less hours (p = 0.490). Nurses with two jobs devoted more time to sleep/rest on the job than those with one job (p = 0.058).…”
Section: Status Quo Of Night-shift Napping Practices Of Nursesmentioning
confidence: 99%
See 3 more Smart Citations